How Does Japan Perceive China as an Adversary? The Dispute in Diaoyu/Senkaku Islands - Prabowo, Muhammad Arif (Nation State: Journal of International Studies, 2021)
A China-Japan grim relationship has been marked by conflicts, and other political security tensions for a long time. One of which is the Diaoyu/Senkaku islands dispute occurring since 2012, it will become an issue for both countries that is difficult to be ironed out. The dispute has occurred since the Japanese government nationalized the islets, which China also claimed. It led to both countries' expansion of military power and a clash in East Asia. This essay aims to analyze how Japan perceives China by focusing on the Diaoyu/Senkaku islands dispute. This article argues Japan perceives China as a threat due to China’s military penetration over Diaoyu/Senkaku islands leading to a strategic distrust of Japan and its uncertain behavior as an international relations actor led to a moral distrust of Japan. This phenomenon will likely raise the tension in the region and enhance the escalation possibility due to the security dilemma effect.